Consumers in Europe. 2009 edition (Luxembourg, 2009)
"The 2009 edition of Consumers in Europe presents a comprehensive set of data and related information concerning consumer markets and consumer protection issues within the European Union. The aim of the publication is to bring together the most relevant and useful information for the evaluation and development of consumer policy, not only as a tool for policy-makers, but also for those interested in end-markets and consumer affairs, such as representative organisations, public authorities, or suppliers of goods and services. Much of the data that has been used will feed into the consumer markets scoreboard which has been designed to monitor outcomes in the single market and to make European Union policy in this area more responsive to the expectations and concerns of consumers. The publication starts with an overview of the single market from the consumer’s perspective, presenting a profile of European consumers and the retail network, as well as issues relating to access and choice, before looking at key indicators for consumption and prices. The overview also presents information on consumer satisfaction, the quality and safety of goods and services, as well consumer representation and protection. The remainder of the publication is devoted to 12 specific consumer markets (for example, food and non-alcoholic beverages, housing, transport, or recreation and culture); each chapter covers one top-level heading within the classification of individual consumption by purpose (COICOP), the main classification used to provide detailed data on consumer prices, price levels and consumption expenditure. The chapters are structured in a similar manner to the overview, in an attempt to present harmonised data and a range of key indicators that may be compared across the publication."